Convexity-preserving scattered data interpolation - Mt Piah, Abd Rahni; Saaban, Azizan; Abd Majid, Ahmad (Jabatan Matematik Universiti Teknologi Malaysia, 2008)
This study deals with constructing a convexity-preserving bivariate C1 interpolants to scattered data whenever the original data are convex. Sufficient conditions on lower bound of Bezier points are derived in order to ensure that surfaces comprising cubic Bezier triangular patches are always convex and satisfy C1 continuity conditions. Initial gradients at the data sites are estimated and then modified if necessary to ensure that these conditions are satisfied. The construction is local and easy to be implemented. Graphical examples are presented using several test functions.